UPAYA PENINGKATAN MINAT DAN PRESTASI BELAJAR IPA SISWA KELAS VIII SMP NEGERI 12 YOGYAKARTA TAHUN PELAJARAN 2012/2013 MELALUI MODEL PEMBELAJARAN KONSTRUKTIVISME - Chairin Najemi; Hidayati Hidayati (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2014)
The purpose of this research was to determine the constructivism learning model in order to increase interest in science learning and achievement of class VIII C of SMP Negeri 12 Yogyakarta in the Academic Year 2012/2013. This type of research is Classroom Action Research (CAR) or Clasroom Action Research (CAR) conducted collaboratively. Subjects in this study were students of class VIII C, amounting to 34 students. Objects in this research is of interest, science learning achievement and learning constructivism. The data collecting technique is conducted by observation, interview, questionnaires engineering, documentation and test. Techniques of data analysis conducted qualitative descriptions. Achievement test data analysis is done by calculating the average and the percentage of successful products. The results showed that after the implementation of this constructivism learningÂ  students' interest in learning has increased. Seen before action students just passively listening to the teacher explain the matter but after being given the actions they have started actively to ask, and discuss with friends. Percentage of student interest obtained from the questionnaire on pre-action that is 63.81%, while the percentage obtained in the first cycle of 71.55%, and the second cycle is obtained percentage of 78.34%. The students also experienced an increase of valueÂ  average 56.65 initial capability, increased in the first cycle to 68.7, and the second cycle increased to 75.92. It can be said that the interest in constructivism learning model and student achievement VIII Class C SMP Negeri 12 Yogyakarta can be improved.